1995
DOI: 10.1136/bmj.310.6975.299
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of 500 consecutive cases of whooping cough: a general practice population study

Abstract: Objective-To describe the natural course of whooping cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 7 publications
2
15
2
Order By: Relevance
“…11 Although Halperin et al 12 and Jenkinson 13 confirmed this finding, our results and other recent studies 9,14,15 showed an even distribution of pertussis between both genders in children. Data from the CDC revealed that up to the age of 15 years, a similar number of boys and girls (50% to 51%) had pertussis, whereas a female preponderance (55% to 69%) was noted in older age groups.…”
Section: Discussionsupporting
confidence: 71%
“…11 Although Halperin et al 12 and Jenkinson 13 confirmed this finding, our results and other recent studies 9,14,15 showed an even distribution of pertussis between both genders in children. Data from the CDC revealed that up to the age of 15 years, a similar number of boys and girls (50% to 51%) had pertussis, whereas a female preponderance (55% to 69%) was noted in older age groups.…”
Section: Discussionsupporting
confidence: 71%
“…Complications included pneumonia, rib fracture, inguinal hernia, severe weight loss and others. Similar ®ndings were reported from a general practitioner in the United Kingdom [77].…”
Section: Diseasesupporting
confidence: 68%
“…Moreover, B. pertussis infection may be a cause of sudden infant death, as has been suggested by epidemiological studies [85,109] and also most recently by demonstration of B. pertussis DNA by PCR in the nasopharynx of deceased infants [66]. In recent years, the fact that pertussis in adolescents and adults is often the source from which infants and children become infected, has received increased attention again [4,16,33,35,52,77,101,108,112,149,150]. However, despite suggestive symptoms, pertussis is frequently not suspected in these age groups and rather``upper respiratory tract infection'' or``bronchitis'' are diagnosed by many primary care providers [100,124].…”
Section: Diseasementioning
confidence: 99%
“…This is in agreement with the findings of Wright et al [2] and Mink et al [3], who concluded that illnesses of patients with pertussis were similar to the illnesses of patients without pertussis. However, in previous studies the diagnosis of B. pertussis infection has for some patients been based on history alone [28,29]. Our study and the studies of Wright et al [2] and Mink et al [3] indicate that the diagnosis of B. pertussis infection should not be based on history alone and that a diagnostic method is needed, at least for adults.…”
Section: Discussioncontrasting
confidence: 50%